Cell-Free Degradation of p27(kip1), a G(1) Cyclin-Dependent Kinase Inhibitor, Is Dependent on CDK2 Activity and the Proteasome - Nguyen, Hoang (American Society for Microbiology, 1999)
Entry into S phase is dependent on the coordinated activation of CDK4,6 and CDK2 kinases. Once a cell commits to S phase, there must be a mechanism to ensure the irreversibility of this decision. The activity of these kinases is inhibited by their association with p27. In many cells, p27 plays a major role in the withdrawal from the cell cycle in response to environmental cues. Thus, it is likely that p27 is a target of the machinery required to ensure the irreversibility of S-phase entry. We have been interested in understanding the mechanisms regulating p27 at the G(1)/S transition. In this report, we define a cell-free degradation system which faithfully recapitulates the cell cycle phase-specific degradation of p27. We show that this reaction is dependent on active CDK2 activity, suggesting that CDK2 activity is directly required for p27 degradation. In addition to CDK2, other S-phase-specific factors are required for p27 degradation. At least some of these factors are ubiquitin and proteasome dependent. We discuss the relationships between CDK2 activity, ubiquitin-dependent, and possibly ubiquitin-independent proteasomal activities in S-phase extracts as related to p27.